Fukushima nuclear disaster : a study in poor crisis communication - Senol Yilmaz (2012)
The Japanese government’s response to the nuclear disaster at Fukushima failed to observe fundamental principles of good crisis communication. It is a striking reminder that advanced planning and training of all stakeholders is necessary to face such challenges.